2019
DOI: 10.1080/2576117x.2019.1656034
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Binocularity in Anisometropic Amblyopia

Abstract: Anisometropic amblyopia is unilateral by definition and current treatment recommendations reflect that characteristic. However, recent research suggests a binocular component that deserves consideration. The aim of this review is to consider the levels of anisometropia deemed amblyogenic, and the cortical changes that occur in the presence of anisometropic amblyopia. Particular attention is given to cortical changes that impact the binocularity of these individuals. Knowledge of binocular deficits in anisometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 83 publications
(142 reference statements)
0
5
0
Order By: Relevance
“…Regardless of positioning accuracy, repositioning is necessary after saccade correction (through overshoot or undershoot). Previous literature regarding cortical damage in amblyopic children [ 16 ] is consistent with a prolonged conduction time that results in increased saccade latency; poor eyesight affects positioning ability, leading to frequent adjustment of the amblyopic eye and increased saccade amplitude. Additionally, saccade latency was significantly longer in children with severe amblyopia than in the other two groups.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…Regardless of positioning accuracy, repositioning is necessary after saccade correction (through overshoot or undershoot). Previous literature regarding cortical damage in amblyopic children [ 16 ] is consistent with a prolonged conduction time that results in increased saccade latency; poor eyesight affects positioning ability, leading to frequent adjustment of the amblyopic eye and increased saccade amplitude. Additionally, saccade latency was significantly longer in children with severe amblyopia than in the other two groups.…”
Section: Discussionmentioning
confidence: 55%
“…During sensitive periods of visual development, long-term suppression can lead to loss of retinal input and a decline in regulatory function [ 14 , 15 ]. Additionally, anisometropia disrupts binocular vision with increasing severity as the degree of anisometropia increases [ 16 ]. Recent studies regarding children with anisometropic amblyopia have focused on diagnoses that involve static vision.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This indicates that the microstructure complexity of bilateral visual radiation in patients with anisometropic amblyopia may decrease, which may be related to the changes in the density, direction, myelin sheath, and other aspects of the visual radiation fiber. In previous studies [ 16 , 17 ], it was confirmed that the cells of the lateral geniculate body of amblyopia are shrunken and their function is impaired and that optic radiation is composed of fibers emitted after the lateral geniculate body. Therefore, the optic radiation of patients with amblyopia may have dysplasia and abnormal fiber projection, which reduces its complexity.…”
Section: Discussionmentioning
confidence: 82%